A Comprehensive Bibliometric Review of Indigenous Knowledge Research - Judijanto, Loso; Gumelar, Sangaji Cokro (Eastasouth Institute, 2025)
This study presents a comprehensive bibliometric review of Indigenous knowledge research from 2000 to 2025, using data retrieved from the Scopus database. Through quantitative mapping with VOSviewer and Bibliometrix, the study examines publication trends, collaboration networks, and thematic developments within the global research landscape. Results reveal three dominant clusters: environmental sustainability and climate resilience; ethnobotany and traditional medicine; and Indigenous health, gender, and social well-being. Australia, Canada, and the United States emerge as leading contributors, while growing participation from Africa, Asia, and Latin America reflects a gradual diversification of epistemic voices. The findings highlight a paradigm shift from descriptive documentation of Indigenous practices to integrative and decolonial research frameworks emphasizing sustainability, equity, and community empowerment. This study contributes to understanding the intellectual evolution of Indigenous knowledge research and provides evidence-based insights for fostering inclusive, cross-cultural collaboration and ethical engagement with Indigenous communities in future scholarship.